The immunologically high-risk kidney recipient in the early post-COVID-19 period. To do or not to do? A case report - Antal, Oana; Daciana Elec, Alina; Muntean, Adriana; Moisoiu, Tudor; Melinte, Razvan Marian; Elec, Florin Ioan (Frontiers in Medicine, 2023)
Kidney transplantation is nowadays the treatment of choice for end-stage kidney disease (ESKD), and it is the most performed organ transplantation. During the COVID-19 pandemic, kidney-transplant recipients appeared to be at higher risk of morbidity and mortality due to severe forms of illness. The result was a decrease in the number of solid organs transplants worldwide, with patients' reduced chance of receiving transplants. The best timing for surgery after COVID-19 infection is still controversial since most of the available data come from study periods with zero or low prevalence of vaccination and COVID-19 variants with high mortality rates. The American Society of Anesthesiologists (ASA) and the Anesthesia Patient Safety Foundation (APSF) Joint Statement on Elective Surgery/Procedures and Anesthesia for Patients after COVID-19 Infection states that elective surgery should be delayed for 7 weeks after a SARS-CoV-2 infection in unvaccinated patients while making no clear statement for vaccinated ones, or those which have already been infected with the virus. Kidney transplant, as opposed to tissue transplant, is not an elective surgery, so the question raised is whether to do it or not. We present the case of a hyper-immunized 47-year-old male patient with end-stage chronic kidney disease who received a second kidney transplant, despite having a mild SARS-COV 2 infection just 2 weeks before his transplantation surgery.